2018
DOI: 10.1007/s10295-018-2017-5
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a synthetic Entner–Doudoroff pathway for enhancing glucose transformation to isobutanol in Escherichia coli

Abstract: Isobutanol as a more desirable biofuel has attracted much attention. In our previous work, an isobutanol-producing strain Escherichia coli LA09 had been obtained by rational redox status improvement under guidance of the genome-scale metabolic model. However, the low transformation from sugar to isobutanol is a limiting factor for isobutanol production by E. coli LA09. In this study, the intracellular metabolic profiles of the isobutanol-producing E. coli LA09 with different initial glucose concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…According to the structural information of proteins and sequence comparisons of homologous proteins, using a rational selection of amino acid residues as targets combined with site-specific mutation of key amino acids, we can screen and obtain target mutants [26][27][28]. Rational design can improve the substrate specificity of an enzyme by remodeling its active pocket, which is the structural domain of the enzyme responsible for its catalytic function and usually consists of a hydrophobic core.…”
Section: Discussionmentioning
confidence: 99%
“…According to the structural information of proteins and sequence comparisons of homologous proteins, using a rational selection of amino acid residues as targets combined with site-specific mutation of key amino acids, we can screen and obtain target mutants [26][27][28]. Rational design can improve the substrate specificity of an enzyme by remodeling its active pocket, which is the structural domain of the enzyme responsible for its catalytic function and usually consists of a hydrophobic core.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, the inactivation of genes concerning byproducts formation, direct evolution of the enzymes in the biosynthetic pathway of isobutanol, and optimization of culture conditions were performed as the general strategies to improve isobutanol production. A study on isobutanol production has demonstrated the use of partially ED pathway-dependent E. coli, which adopted the ED pathway derived from Z. mobilis [16]. However, the strain used in that study was simply introduced to the genes concerning the ED pathway, and the redox balance in the biosynthesis pathway involved in converting glucose to isobutanol was not completely considered.…”
Section: Discussionmentioning
confidence: 99%
“…1). Although isobutanol has reportedly been produced using E. coli carrying a synthetic ED pathway of Z. mobilis [16], the EM pathway and pentose phosphate pathway (PPP) has remained in the metabolic pathway of E. coli used in the report; this indicates that the metabolic pathway for isobutanol production involving the ED pathway should be improved from the perspective of redox balance.
Fig. 1The synthetic metabolic pathway for isobutanol production in E. coli.
…”
Section: Introductionmentioning
confidence: 99%
“…Other efforts have focused on increasing isobutanol production from glucose. Liang et al (2018) introduced the heterologous Entner-Doudoroff (ED) pathway from Z. mobilis to increase glucose transformation to pyruvate for enhanced precursor accumulation. The resulting E. coli strain, ED02, produced 13.67 g/L isobutanol with a productivity of 0.456 g/L/h, a 56.8 and 88.1% improvement over the parent strain, respectively.…”
Section: C3-c4 Alcohol Tolerance and Production In E Colimentioning
confidence: 99%